Comparative Study on Information Retrieval Approaches for Text Mining - Vishakha D, Bhope; Sachin N, Deshmukh (International Journal of Computer Sciences and Engineering, 2015)
Text mining is the process of extracting information form unstructured to structured text data. The challenging issue in text mining is to extract user required information in efficient manner. To perform this task various data mining methods are used in which the text document analyzed on the basis of term, phrase, concept and pattern. This paper studies the text representation methods and basic term weighing schemes. Ruled-based Phrase Extraction method and Sequential Pattern mining method are discussed to improve the system performance for finding relevant and interesting information.